2018
DOI: 10.3390/su10051471
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ecological Restoration Projects in Dry Lands: Data-based Assessment and Human Perceptions in the Lower Reaches of Heihe River Basin, China

Abstract: Desertification is a critical environmental problem in China's northwestern region. In this context, since the early 2000s, projects targeting ecological restoration have been implemented in the lower reaches of the Heihe River basin. Using multi-scale remote sensing data and field observations, this paper examines the outcomes of the ecological restoration projects. Specifically, this paper examines the vegetation change through remote sensing and local perceptions of the projects through semi-structured ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A series of desertification control projects (DCPs) represent China's great efforts to combat desertification, such as the Grain for Green Project, the Natural Forest Conservation Project, and the Beijing-Tianjin Wind and Sand Source Control Project [12,13]. At the same time, many lower-level governments have also carried out a number of projects to control desertification on the basis of regional characteristics, which are complementary to the central government's projects [14]. All the DCPs have achieved desertification control, especially in terms of the increase of vegetation coverage [15].…”
Section: Introductionmentioning
confidence: 99%
“…A series of desertification control projects (DCPs) represent China's great efforts to combat desertification, such as the Grain for Green Project, the Natural Forest Conservation Project, and the Beijing-Tianjin Wind and Sand Source Control Project [12,13]. At the same time, many lower-level governments have also carried out a number of projects to control desertification on the basis of regional characteristics, which are complementary to the central government's projects [14]. All the DCPs have achieved desertification control, especially in terms of the increase of vegetation coverage [15].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation, being a crucial constituent of arid ecosystems, serves as a perceptible manifestation of the natural milieu and a comprehensive representation of the regional ecological environment. The restoration of vegetation stands as a paramount approach in rehabilitating mining areas [30], while also serving as a direct and pivotal indicator for assessing land degradation attributes [31]. This article employed the concept of vegetation community succession and limiting factors to propose a method for categorizing the restoration stage of arid mining areas, with vegetation growth serving as a crucial criterion.…”
Section: An Evaluation System Of the Stepwise Ecological Restoration ...mentioning
confidence: 99%
“…Muriithi et al [18] investigated the trends in the average annual NDVI before and after the presumed onset of rapid horticulture in the central highlands of Kenya, and the authors further analyzed the relationship between the average annual NDVI and specific driving factors, such as population density, large-scale commercial farms, and mean annual rainfall in sub-watersheds. It can be seen that international scholars are devoting more attention to the influence of climatic factors and human activities on vegetation changes, and some studies have indicated that ecological construction projects have greatly influenced vegetation changes [19][20][21]. However, most of these studies have focused only on qualitative descriptions; thus, it is necessary to quantitatively analyze the relative contributions of climate change and human activities to changes in vegetation [22].…”
mentioning
confidence: 99%